2012
DOI: 10.1186/1472-6920-12-34
|View full text |Cite
|
Sign up to set email alerts
|

Comparative cross-sectional study of empathy among first year and final year medical students in Jimma University, Ethiopia: Steady state of the heart and opening of the eyes

Abstract: BackgroundThere is general consent that empathy is crucial for the physician-patient relationship and thus an important issue in medical education. This comparative study was designed to examine the differences in empathy between first year and final year medical students in Jimma University, Ethiopia.Methods A comparative cross-sectional study among 131 first year and 106 final year medical students was conducted in Jimma University, Ethiopia on academic year 2010/11. The study subjects were selected using si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
52
0
7

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(61 citation statements)
references
References 32 publications
2
52
0
7
Order By: Relevance
“…This indicates acceptable internal consistency of the RMET in Poland; thus, it is a reliable tool that measures mindreading in adults. Reliability, which was reported in past studies of the RMET, was .58 to .70 (Voracek & Dressler, 2006;Harkness et al, 2010;Dehning, Girma, Gasperi, Meyer, Tesfaye, & Siebeck, 2012;Vellante, Baron-Cohen, Melis, Petretto, Masala, & Preti). Additionally, the test-retest stability of the Polish version of RMET was acceptable, with interclass correlation coefficients equaling 0.886.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…This indicates acceptable internal consistency of the RMET in Poland; thus, it is a reliable tool that measures mindreading in adults. Reliability, which was reported in past studies of the RMET, was .58 to .70 (Voracek & Dressler, 2006;Harkness et al, 2010;Dehning, Girma, Gasperi, Meyer, Tesfaye, & Siebeck, 2012;Vellante, Baron-Cohen, Melis, Petretto, Masala, & Preti). Additionally, the test-retest stability of the Polish version of RMET was acceptable, with interclass correlation coefficients equaling 0.886.…”
Section: Discussionmentioning
confidence: 51%
“…On the basis of the Empathy Quotient results, it is difficult to separate cognitive and affective empathy, with the former being theoretically related to the Theory of Mind (Rogers et al, 2007). Therefore, it is not surprising that the majority of validation studies did not report the analysis of theoretical convergence between the Empathy Quotient and the RMET (Ethiopian version, Dehning et al, 2012;Hungarian version, Kelemen, Keri, Must, Benedek, & Janka 2004;Japanese version, Kunihira, Senju, Dairoku, Wakabayashi, & Hasegawa 2006;Turkish version, Yildirom et al, 2011;Swedish version, Hallerbäck, Lugnegard, Hjarthag, & Gillberg, 2009). …”
Section: Discussionmentioning
confidence: 99%
“…Dehning et al in a study of Ethiopian medical students also had found that males had lower empathy than females. 24 However, when compared semester wise the results are more interesting (Table 5). There is no significant difference among female students in different semesters it thereby implying that the decline in empathy scores in third and seventh semester (those entering the fourth year) is entirely because of significant decline in empathy scores among male students.…”
Section: Discussionmentioning
confidence: 98%
“…Similar results were obtained from many previous studies (Hojat et al 2004;Kliszcz et al 2006;Kataoka et al 2009;Hojat et al 2009b;Neumann et al 2011;Quince et al 2011;Tavakol et al 2011;Chen et al 2012;Paro et al 2012;Hasan et al 2013;Wen et al 2013;Leombruni et al 2014;Youssef et al 2014;Hojat & Gonnella 2015) . However some studies did not find such kind of differences (Colliver et al 2010;Rahimi-Madiseh et al 2010;Dehning et al 2012). Studies from Turkey revealed a decline in empathy throughout the medical study years (Gonullu & Oztuna 2012;Sen et al 2014).…”
Section: Discussionmentioning
confidence: 99%